The Effect of Education on Knowledge and Attitude of Pain Self-Medication at Pamengpeuk Village - Sitti Fatimah Putri Hasyul; Risa Susanti; Genialita Fadhilla; Ahsani Siti Sadiyah (Indonesian Journal of Community Empowerment (IJCE), 2022)
Abstract The majority of Indonesian people are familiar with self-medication. Pain is one of the symptoms of the disease that can be overcome through self-medication. public knowledge about self-medication is still relatively poor and self-medication behavior in Indonesia is still running irrationally. The purpose of this study was to determine the effect of providing education on knowledge and attitudes of using analgesic drugs for pain self-medication. This study used a pre-experimental design, with a one group pretest posttest design. The instrument used is a questionnaire that has been tested for validity and reliability. The results showed that there were differences in the level of knowledge and attitudes after giving education (p<0.05). Education on the use of analgesics for pain self-medication showed an increase in the level of knowledge and attitudes of respondents. Abstrak Masyarakat Indonesia mayoritas sudah mengenal swamedikasi. Nyeri merupakan salah satu gejala penyakit yang dapat diatasi melalui swamedikasi. pengetahuan masyarakat mengenai swamedikasi masih tergolong buruk dan perilaku swamedikasi di Indonesia masih berjalan tidak rasional. Tujuan dari penelitian ini mengetahui pengaruh dari pemberian edukasi terhadap pengetahuan dan sikap penggunaan obat analgesik untuk swamedikasi nyeri. Penelitian ini menggunakan desain praeksperimental, dengan rancangan one group pretest posttest. Instrumen yang digunakan berupa kuesioner yang telah diuji validitas dan reabilitasnya. Hasil penelitian menunjukkan terdapat perbedaan tingkat pengetahuan dan sikap setelah pemberian edukasi (p<0,05). Edukasi penggunaan analgesik untuk swamedikasi nyeri menunjukkan peningkatan tingkat pengetahuan dan sikap responden.